Heart rate response to a climber`s fall in sport climbing - Chaloupsky, D. (Journal of Human Sport & Exercise, 2015)
The research deals with response of heart rate to a climber`s simulated fall in a leading position when indoor climbing. Heart rate of climbers was recorded during ascents of an overhanging route in the leading position, to the given point high above the ground, followed by falling into the last protection. The length of the free fall was defined by the place of the last belay anchor, which was at the height of climber`s ankles. The length of the fall was about two meters of free fall plus the consequent rope shift in dynamic belaying system. The total length of the fall was 3 to 6 meters, depending on the dynamic belaying. The sample comprised 14 participants at the age of 16 - 43; 12 men and 2 women; all the participants were advanced climbers experienced with a fall in the position of a lead. Heart rate values observed during the fall did not significantly exceed the heart rate values during the actual climbing, when climbers usually reach 84 - 96% of their maximal heart rate (1 exception). The results of the analysis suggest inter-individual differences in heart rate response to the load when climbing and subsequently falling, particularly during the fall and also in the recovery of the actual fall.